Spain in the international urban networks around the First World War - Garcia Gonzalez, Maria Christina; Guerrero, Salvador (International Planning History Society Proceedings, 2018)
The neutrality of Spain during First World War brought with it a significant economic growth. Then, Spain timidly joined the town planning forums of meetings, debates and exchanges that took place in the post-war European era. Some Spanish public institutions as the Instituto de Reformas Sociales, responsible for the social housing policy, and the City Councils of Madrid, Barcelona and Bilbao, which tried to order their development; private institutions such as the Compañía Madrileña de Urbanización, promoter of the Madrid Linear City by Arturo Soria, and the Civic Society Ciudat Jardí in Barcelona, diffuser of the Garden City movement in Catalonia; and the first Town Planning Professor in the School of Architecture of Madrid, César Cort, attended different congresses looking for a solution to the housing problem along with the town planning extension issue. The aim of this paper is to show the Spanish town planners and technicians who participated in the international urban networks in order to consolidate the Spanish urbanism through the new technical, theoretical and legal tools that were being implemented in Europe. They also attended to proudly show some Spanish advances.